Sur un extrait du film documentaire Les champignons hallucinogènes du Mexique (1964) : art sous influence et transformation de la personnalité - Vincent Verroust (Histoire, Médecine et Santé)
This article analyzes an excerpt from the documentary Les champignons hallucinogènes du Mexique (Hallucinogenic Mushrooms of Mexico), directed in 1964 by Pierre Thévenard under the scientific guidance of Professor Roger Heim, a mycologist and then-director of the National Museum of Natural History. This rarely broadcast film explores the archaeological, historical, ethnographic, biological, psychological, and philosophical dimensions of hallucinogenic mushrooms, which had recently been rediscovered by the Western scientific community. The studied excerpt highlights the experiences of a volunteer, Mr. Esnault, who, under the influence of psilocybin, develops unexpected artistic talents, suggesting a transformative potential of these substances. The article also discusses the philosophical and spiritual implications of these experiences, emphasizing their relevance in the current context of the “Psychedelic Renaissance.”